The Administrative Judiciary Reforms in Poland - Kamiński, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The study concerns the factors influencing the shape of the Polish administrative judiciary, ranging from their conceptual patterns in the interwar period to the present day. Therefore, the article presents the history of administrative judiciary reforms as well as the constitutional and statutory foundations of the Polish administrative judiciary and their most important changes. The following parts of the study discuss issues related to the structure and internal organization of administrative courts, their jurisdiction and the concept of “administrative court case” as the subject of proceedings before an administrative court. The basic principles of administrative court proceedings as well as the types and nature of court decisions, including their appealability, validity and enforceability, were also discussed. The last part highlights the challenges faced by the Polish administrative judiciary and the prospects for its further reforms.